1991
DOI: 10.1007/bf03259745
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of BRB-I-28 (7-benzyl-7-aza-3-thiabicyclo[3.3.1]nonane hydroperchlorate), a Novel Antiarrhythmic Agent

Abstract: SummaryThe aim of this study was to characterise the pharmacokinetic disposition and tissue distribution of BRB-I-28 (7-benzyl-7-aza-3-thiabicyclo[3.3.l)nonane hydroperchlorate) in rats. The pharmacokinetic disposition was studied by collecting blood samples before and at frequent intervals after intracardiac or oral administration of 14C-labelled BRB-I-28. Two-compartment and I-compartment pharmacokinetic models were used to describe blood concentration-time profiles after intracardiac and oral administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In a study of the properties of these compounds as local anesthetics, we found that 7-(3-butoxypropyl)-3thia-7-azabicyclo[3.3.1]nonane hydrochloride (10) [11] is superior to the lidocaine standard in duration of anesthesia. As expected [12,13], the 7-alkoxyalkyl-3-thia-7-azabicyclo[3.3.1]nonane products have antiarrhythmic activity. Of all the compounds compared, the most active compound preventing calcium chlorideinduced cardiac arrhythmia and on a model of fatty occlusion of the coronary artery is 7-(2-ethoxyethyl)-3-thia-7-azabicyclo[3.3.1]nonane (8) [9].…”
supporting
confidence: 67%
See 1 more Smart Citation
“…In a study of the properties of these compounds as local anesthetics, we found that 7-(3-butoxypropyl)-3thia-7-azabicyclo[3.3.1]nonane hydrochloride (10) [11] is superior to the lidocaine standard in duration of anesthesia. As expected [12,13], the 7-alkoxyalkyl-3-thia-7-azabicyclo[3.3.1]nonane products have antiarrhythmic activity. Of all the compounds compared, the most active compound preventing calcium chlorideinduced cardiac arrhythmia and on a model of fatty occlusion of the coronary artery is 7-(2-ethoxyethyl)-3-thia-7-azabicyclo[3.3.1]nonane (8) [9].…”
supporting
confidence: 67%
“…C (11) C (12) C (13) The 13 C NMR spectra of the pure isomers given in Table 2 lack a singlet for the carbonyl carbon atom but show a doublet for C (9) at 68.2-72.3 ppm. The 13 C NMR spectra of 14 and 15, which are unresolved isomer mixtures, show doubling of the carbon atom signals for the ring and substituent.…”
mentioning
confidence: 99%
“…Pharmacokinetic and tissue distribution profiles of BRB-I-28 in rats (13) and in dogs (14) have been examined. Previous results have shown that BRB-I-28 has a bioavailability of only 44.5% in dogs, and may undergo extensive metabolism (14).…”
Section: Introductionmentioning
confidence: 99%